Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1001/jamapsychiatry.2016.1243
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Religious Service Attendance and Lower Suicide Rates Among US Women

Abstract: In this cohort of US women, frequent religious service attendance was associated with a significantly lower rate of suicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
111
1
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 30 publications
(49 reference statements)
11
111
1
8
Order By: Relevance
“…We selected covariates considered potentially important predictors for multimorbidity and HRQOL . These included age, race, body mass index, smoking status, geographic region, alcohol intake, coffee intake, marital status, and living alone.…”
Section: Methodsmentioning
confidence: 99%
“…We selected covariates considered potentially important predictors for multimorbidity and HRQOL . These included age, race, body mass index, smoking status, geographic region, alcohol intake, coffee intake, marital status, and living alone.…”
Section: Methodsmentioning
confidence: 99%
“…Of course, such an analysis is also potentially cofounded by affiliation, with Northern Europe predominantly Protestant, Southern Europe predominantly Catholic and Western Europe mixed. This issue may, however, not be especially problematic insofar as there is relatively little evidence that associations between religious service attendance and health vary by Catholic versus Protestant affiliation, except for the outcome of suicide [3335]. In any case, it does not seem that the analyses of Ahrenfeldt et al add much evidence either for or against the hypothesis that associations with health are stronger in areas that are themselves more religious.…”
Section: Broader Cultural Contextsmentioning
confidence: 99%
“…Again other mechanisms seem to be present. Current evidence from longitudinal studies suggests that service attendance is subsequently associated not only with all-cause mortality but also with less smoking, alcohol abuse, and drug use [1,38]; less depression and lower suicide rates [1,3,10,34,35]; greater meaning and purpose [39]; great optimism [27]; greater happiness and life-satisfaction [21]; lower crime [40,41]; greater social support and greater likelihood of developing a more extensive social and friendship network [21,25,27] as well as lower likelihood of divorce [25,42,43]. The mechanisms by which religious participation affects health may thus be numerous and quite diverse, and current evidence thus perhaps suggests that it may be the small contribution of many different pathways, rather than the substantial contribution of any specific one, that supplies religious service attendance with its powerful effects on health.…”
Section: Other Mechanisms For Religion and Healthmentioning
confidence: 99%
“…The weak correlation and positive relationship to suicidal ideation may be related to the 10 congregants who reported attending more than one service per week and also reported high SOC and some suicidal ideation. While VanderWeele et al (2016) found that frequent religious service attendance was associated with substantially lower suicide risk and Rushing et al (2013) found that more frequent attendance at religious activities was associated with decreased current suicidal ideation, a relationship which remained significant when social support was added to the model, in this sample it was not strongly related to lower suicidal ideation. have reported that religious service attendance is not especially protective against suicidal ideation.…”
Section: Hypothesis 1: Soc Is Related To Less Suicidal Ideationmentioning
confidence: 61%
“…Religion and spirituality (R/S) are associated with greater physical and mental health (Koenig et al 2012) including less suicidal ideation (Bearman and Moody 2004;Blackmore et al 2008;Cohen et al 2008;Cook et al 2002;Greening and Stoppelbein 2002;Pienaar et al 2007), fewer suicide attempts (Burshtein et al 2016;Nonnemaker et al 2003;Thompson et al 2007), and fewer suicide deaths (Barranco 2016;Hilton et al 2002;Nisbet et al 2000;VanderWeele et al 2016). However, the relationship between R/S and suicidal behaviors is complex .…”
mentioning
confidence: 99%